British propaganda and the threat from Chinese communism, 1948-54. - Griffiths, Katie (2019)
On the 6th January 1950 Britain accorded de jure recognition to the newly formed People’s Republic of China. The decision reflected a post war desire in Britain to protect its trade with China and the security of colonial Hong Kong. Yet in seeking diplomatic relations with a communist country, it not only diverged from its American ally, but appeared at odds with its own commitment to combat the perceived threat of communism. It is within this set of conflicting interests that the thesis is positioned.